Biomechanical Effects of Tibial Plateau Levelling Osteotomy on Joint Instability in Normal Canine Stifles: An In Vitro Study - Shimada, Masakazu; Takagi, Tetsuya; Kanno, Nobuo; Yamakawa, Satoshi; Fujie, Hiromichi; Ichinohe, Tom; Suzuki, Shuji; Harada, Yasuji; Hara, Yasushi (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of the study was to determine the changes in biomechanical characteristics following tibial plateau levelling osteotomy (TPLO) using simulated manual tests.Study Design Twenty-one stifles from healthy Beagle dogs that had undergone TPLO or had not (control) were first tested in the intact form, and then the cranial cruciate ligament (CrCL) was transected in each to provide four test situations: control-intact, control-CrCL-transected, TPLO-intact and TPLO-CrCL-transected. The stifles were then analysed using a robotic joint biomechanical testing system. The craniocaudal drawer, axial rotation and proximal compression tests were applied.Results The craniocaudal displacement during the drawer test was not significantly different between the control-intact and TPLO-intact. However, the displacement was significantly greater in the TPLO-CrCL-transected than in the control-intact. In the axial rotation test, the internal–external (IE) rotation was significantly greater in the TPLO-intact than in the control-intact. Similarly, the IE rotation was significantly greater in the TPLO-CrCL-transected than in the control-CrCL-transected. In the proximal compression test, craniocaudal displacement was not significantly different among the control-intact, TPLO-intact and TPLO-CrCL-transected.Conclusion These findings suggest that TPLO influences the tension of the collateral ligaments and might generate laxity of the tibiofemoral joint. Instability after the osteotomy might be associated with the progression of osteoarthritis.
Keywords: dog; biomechanical effect; six-degree-of-freedom robotic testing system; cranial cruciate ligament; tibial plateau levelling osteotomy